MODELS AND METHODS FOR SYNTHESIS OF MANUFACTURING PROCESS STRUCTURE FOR MACHINING AT FLOW LINE OF STATIONARY MACHINES - N. N. Guschinsky; O. Battaia; A. Dolgui (Informatika)
A problem of design of a flow line composed of stationary machines is considered. Mathematical models and methods for synthesis of manufacturing process structure are proposed. The models take into account main technological and structural constraints with the criterion of minimizing the line equipment cost. A decomposition scheme for solving the initial problem and its formulation in terms of a mixed linear problem are developed. Computational results are also presented.